ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI TENAGA KERJA BONGKAR MUAT (TKBM) JASA KARYA PELABUHAN PONTIANAK - B11110143, Muhammad Said (Jurnal Manajemen Update, 2015)
This research is intended to know the influence of service quality (tangible, reliability, responsiveness, assurance, and empathy) either partially or simultaneous to the cooperation members’ satisfaction and to know the more dominant influence from quality service (tangible, reliability, responsiveness, assurance, and empathy) to the members cooperation satisfaction of Labor Loading Unloading (TKBM) Jasa Karya Pontianak Port. The population in this study is members cooperation of Labor Loading Unloading (TKBM) Jasa Karya Pontianak Port. The research sample using non-probability sampling technique with accidental sampling approach some 100 people. Technique analysis used is linear regression analysis of multiple with using program spss version 20.0. The result of study shows that service quality can be seen from 5 dimension: tangible, reliability, responsiveness, assurance, and empathy as simultaneous and partial. Significant influence to the members cooperation satisfaction of Labor Loading Unloading (TKBM) Jasa Karya Pontianak Port. is the variabel which significantly has a dominant influence on the responsiveness. With the value of determination coefficient (R Square) 48,5% it means that the independent variable may describe the dependent variable, while the remaining 51,5% is explained by the other independent variables which are not included in the this study model. Keywords : Quality Of Service, Tangible, Reliability, Responsiveness, Assurance, Empathy And Satisfaction Of Member